Exercise or physical activity-related adverse events in people receiving peritoneal dialysis: A systematic review. Issue 5 (September 2022) - Tarca, Brett; Jesudason, Shilpanjali; Bennett, Paul N; Kasai, Daiki; Wycherley, Thomas P; Ferrar, Katia E
People receiving peritoneal dialysis (PD) may benefit from participation in exercise or physical activity. However, exercise therapy for people receiving PD is not typically included in routine care, in part, due to ongoing uncertainties about risk. The aim of this review was to systematically collate and explore data on adverse events experienced by people receiving PD while undertaking an exercise or physical activity intervention. Searches yielded 25 exercise or physical activity intervention studies involving people receiving PD. Of these 25 studies, 17 studies provided adverse event data and were included in the final review. No serious adverse events (e.g. death, hospitalisation) were found attributable to the intervention. From 50 reported adverse events during the intervention period, 32 were attributable to the exercise or physical activity intervention with most being musculoskeletal (e.g. muscle/joint pain, etc.) followed by fatigue. Most events were mild to moderate in severity and resolved by exercise programme modification, education, rest or medication. The results from this review did not uncover signals of harm for people receiving PD who engage in exercise with risk of adverse events appearing to be low, however, improved adverse events reporting and further interventional studies are required before robust guidelines can be produced.